TOURIST ARRIVALS AND OVERNIGHT STAYS IN HOTELS IN ROMANIA DURING THE COVID-19 PANDEMIC VERSUS 2019 AND FUTURE TRENDS IN 2022 - Agatha POPESCU; Adelaida Cristina HONTUS; Mirela STANCIU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The paper analyzed the dynamics of tourist arrivals and overnight stays in Romania during the COVID-19 pandemic versus 2019 and expectations in 2022. The methodology includes dynamics and structural indices and regression equations. Of the highest performance achieved in 2019, tourist demand declined to 48% in 2020 and 65% arrivals in 2021, and to 64% and 67% overnight stays. Hotels accounted for 64-67% in total arrivals and 45- 64% in stays. The Romanians' share during the pandemic was 92.9% in 2020 and 85.2% in 2021. In hotels, their weight 69%. The polynomial equations showed a parabolic trend of arrivals and stays by month. Thus, 2021 was a better year than 2020 and in 2022 it is expected that arrivals to represent 85% of the 2019 level. In 2022, 941 new 5 stars hotels will be built to assure more comfort and accommodation capacity. Hotel managers have to use creative and efficient methods to attract more tourists. Offer diversification, customized packages, bonuses, price flexibility, high quality services, an intensified virtual promotion (web-site, social media) could attract more visitors and improve hotels performance.